Interferensi Manusia untuk Melestarikan Alam pada Novel Karya Charlotte McConaghy Once There Were Wolves - Firda Aulia Rachmasari; Muhammad Edy Thoyib (UIN Alauddin Makassar, 2023)
Environmental problems have become a severe issue in recent decades. The world has started to change due to human activities that affect the natural environment. Deforestation, industrialization, burning fuels, human overpopulation, and many more have triggered climate change. In her novel, Once There Were Wolves, Charlotte McConaghy vividly describes such a condition. This novel exposes how the Scottish Highlands begins to ruin because of the overabundant population of deer. They eat the plant shoots, and that makes the plants die. Moreover, this research intends to investigate human interferences in saving damaged nature as depicted in the novel. This study is a literary criticism since it aims to analyze the object used. Furthermore, the Ecocriticism approach was employed to analyze humans' efforts to help nature return to its natural state. The research method involves a deep reading and understanding of Charlotte McConaghy’s Once There Were Wolves, with a focus on the humans’ effort to rewild nature. The result reveals the portrayal of humans’ actions to help nature back into its natural state by releasing wolves as the apex predator, keeping the forest and vegetation, and finding places to grow trees. Doing those actions helps the Scottish Land back naturally. The deer population decreases and the land becomes a beautiful place to go.